Hybrid Si nanocones/PEDOT : PSS solar cell - Wang, Hao (2015)
Periodic silicon nanocones (SiNCs) with different periodicities are fabricated by dry etching of a Si substrate patterned using monolayer polystyrene (PS) nanospheres as a mask. Hybrid Si/PEDOT:PSS solar cells based on the SiNCs are then fabricated and characterized in terms of their optical, electrical, and photovoltaic properties. The optical properties of the SiNCs are also investigated using theoretical simulation based on the finite element method. The SiNCs reveal excellent light trapping ability as compared to a planar Si substrate. It is found that the power conversion efficiency (PCE) of the hybrid cells decreases with increasing periodicity of the SiNCs. The highest PCE of 7.1% is achieved for the SiNC hybrid cell with a 400-nm periodicity, due to the strong light trapping near the peak of the solar spectrum and better current collection efficiency.